Predictors of adherence to antiretroviral therapy among PLHIV - Arjunahalli Eswarachar Paramesha; Leena Kunnath Chacko (Wolters Kluwer Medknow Publications, 2019)
Adherence to antiretroviral therapy (ART) is of paramount importance to achieve the optimum control of viral load and progression of disease among people living with HIV (PLHIV). An overview of systematic reviews to summarize the factors influencing adherence to ART was not found in the literature; hence, the systematic review of systematic reviews was conducted to provide global view of factors influencing adherence to ART. Systematic reviews ever published till May 2018 were searched and retrieved between May 2015 and May 2018 from Cochrane and PubMed databases. Among 88 studies initially chosen based on inclusion and exclusion criteria, 22 were selected for further analysis. Qualitative analysis of included reviews was made through narrative synthesis approach. Results of the study show that among the 60 factors enlisted, 5 were most highly significant, 7 were highly significant, 19 were moderately significant, and 29 were emerged as significant factors. Substance abuse, financial constraints, social support, HIV stigma, and depressive symptoms were the most highly significant factors influencing the adherence, whereas age, employment status, long distance, side effects of drugs, pill burden, education, and mental health were regarded as highly significant factors influencing ART. Fatigue, away from home, being too busy in other things, simply forgot, and beliefs about the necessity of ART emerged as significant factors. The study concludes that findings from the overview give global insight into the factors determining adherence to ART which would further influence the innovations, program, and policy-making to mitigate the problem of nonadherence.